KONSERVATISME AKUNTANSI : LEVERAGE, LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN - Ogie Sanjaya; Muhammad Teguh Prasetyo; Ria Puspitasari; Ririen Nooraeni (Jurnal Comparative: Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of Leverage, Liquidity, Profitability and Company Size on Accounting Conservatism in food and beverage sub-sector companies on the Indonesia Stock Exchange (IDX). The research period used was 5 years, namely the period 2013-2017. The population of this study includes food and beverage companies listed on the Indonesia Stock Exchange for the 2013-2017 period. The sampling technique used purposive sampling technique. Based on the criteria set, the number of 9 companies is obtained. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The analytical method used is panel data regression analysis. The results showed that partially Leverage and Liquidity had no effect on Accounting Conservatism, while Profitability and Firm Size had an effect on Accounting Conservatism.